Polska subkultura otaku wobec źródeł japońskich - Rutkowska, Małgorzata (Załącznik Kulturoznawczy, 2023)
Japanese otaku is a geek or nerd, who is strongly dependent on the products of Japanese pop culture from the circle of anime and manga. Such a unit subjugates all other areas of life to this passion, which means that he or she is willing to sacrifice everything for cultivating the interest, which from an ordinary hobby turned into a way of life. Japanese otaku has their own world, a virtual one, which often causes problems with establishing contacts with the real world. Polish otaku however is only a fan, a person who has a unique hobby. Such a person does not sacrifice everything to their hobby and only treats it as something you an do in your free time. He or she is able to reconcile reality with fiction without sacrificing any of them. Such great differences between the two subcultures of otaku are due to different mentality of their members and various understanding of the term otaku. This causes different treatment of themselves and ways in which both subcu tures otaku manifest themselves. Furthermore, the lack of awareness about Japanese otaku subculture in the minds of the representatives of Polish otaku subculture results in the creation of the group completely different from its original.